DEKOMPOSISI KETIMPANGAN PENDAPATAN DAN DETERMINAN POSISI EKONOMI - Diah Mekita Sari; Dwi Rizky Syaifullah (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2021)
High inequality between regions is one of the causes of high income inequality and hampered economic growth in NTT Province. The purpose of this study is to analyze the inequality between regencies within and cross islands, also the factors that affect economic position of every regency in NTT Province. This study uses data from BPS’s publication and DJPK website. Descriptive analysis using Theil's Index to decompose income inequality and Klassen's Typology to classify economic positions. Inference analysis using Multinomial Logistic Regression is to analyze the determinants of economic position of each regency. Analysis with Theil’s Index shows that main cause of inequality between regencies is inequality between regencies within island, while inequality cross islands is relatively low. The centralization of the economy in several regencies within each island is the cause of high income inequality between regencies. The quality of human resources has significant effect on increasing the tendency of regency that are in economic position of underdeveloped regions to become regions with fast progress and fast growing classification or developed but depressed regions classification. Therefore, improving the quality of human resources is a way that can be done to reduce income inequality between regencies in NTT Province.